Records of morphological abnormalities in the Brazilian electric ray Narcine brasiliensis (Olfers, 1831) (Chondrichthyes: Narcinidae) in the southwestern Atlantic - Rolim, Fernanda Andreoli [UNESP]; Rotundo, Matheus Marcos; Stabile, Gustavo Cardoso; Vaske-Júnior, Teodoro [UNESP] (Springer Nature, 2020)
This study provides the first record of external morphological deformities in Chondrichthyes of the family Narcinidae. We report here abnormalities in two individuals of Narcine brasiliensis (Olfers, 1831), in which one of them had its pectoral fins not fused with the head and the other presented anophthalmia, with the left eye absent. Possible causes, including the high concentration of pollutants in the region, are briefly discussed.
Keywords: Anophthalmia; Embryonic development; Fins not adherent; Torpediniformes